1975
DOI: 10.1111/j.1751-1097.1975.tb06646.x
|View full text |Cite
|
Sign up to set email alerts
|

pH DEPENDENCE OF SINGLET OXYGEN PRODUCTION IN AQUEOUS SOLUTIONS USING THIAZINE DYES AS PHOTOSENSITIZERS

Abstract: The production of singlet oxygen by thiazine dye photosensitization, as measured by the rate of photooxidation of tryptophan, was found to be very sensitive to changes of pH in the range 5-9. For methylene blue in aerated solutions, the production of 'O,* is approximately five times more efficient in basic than in acidic medium. This was shown to be related to the pK's of the triplet dyes, by evaluating the yields of '02* from the lifetimes and the quenching rate constants for the two ionic species of sensitiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1
1

Year Published

1975
1975
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(51 citation statements)
references
References 21 publications
1
48
1
1
Order By: Relevance
“…The efficiency of the '08 production by dyes can be correlated with the energy difference between the dye triplet state and '08, and in methylene blue solutions the pH dependence of the '0% yield is related to the p K s of the excited dye [6]. The interaction between '0: and amino acids has been studied in well defined conditions by Matheson et al with lasergenerated '0$ [8,41].…”
Section: Anaerobic Photosensitization Of Proteinsmentioning
confidence: 99%
“…The efficiency of the '08 production by dyes can be correlated with the energy difference between the dye triplet state and '08, and in methylene blue solutions the pH dependence of the '0% yield is related to the p K s of the excited dye [6]. The interaction between '0: and amino acids has been studied in well defined conditions by Matheson et al with lasergenerated '0$ [8,41].…”
Section: Anaerobic Photosensitization Of Proteinsmentioning
confidence: 99%
“…2B shows the titration curves for the two processes compared with the pH curve for the O 2 ( 1 ⌬ g ) quantum yield resulting from the energy transfer from 3 MB ϩ * (triplet MB ϩ ) to O 2 in the triplet ground state O 2 ( 3 ⌺ g-) and obtained from Ref. 37. In this work, the authors demonstrated that the quantum yield of 3 MB ϩ * produced by irradiation and the generation of O 2 ( 1 ⌬ g ) by energy transfer both obey the same pH curve, since the former gives rise to the latter.…”
Section: Effect Of Ph On O 2 ( 1 ⌬ G )-Induced Oxidative Modificationmentioning
confidence: 99%
“…Results obtained at different pH's thus become very difficult to compare. Buffering the solutions to fix the pH has its drawbacks also, since the buffer tends to modify the results, as has been observed in the singlet oxygen production in thiazine photosensitization studies ( 5 ) . If one adds to this the fact that tumor cells have a lower pH than normal cells, it clearly becomes apparent that knowledge of the ionic distribution diagrams, along with quantitative information on any dimerization/aggregation process, becomes a prerequisite to…”
Section: Introductionmentioning
confidence: 99%